(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The article is about faith and conviction for improving the human usage of fundamental freedoms for all people from the world’s networks. In this study, the question of religion and belief in the turn of events is explained. This article included scientific methods for analysts to refer to books they were debating (religion and belief in the human turn of events), which they later analyzed and explained in amazing fashion. This study is considered a doctrinal study, in which the expert depended on reports, books and updates and subjected them to logical research to the ideal results. With regard to the subtopics to be discussed in this review, they are misunderstandings about the Vedas and illuminate the overall picture of what is the new age religion, its impact on the current generation and what this "secularism" guardian is about. At this point, the result will be integrated, the most important being that the globe needs cooperation for compassionate interests and human turn of events.